Modeling Premature Ejaculation Disorder Based on Body Image with the Mediating Role of Attachment and Narcissism - Zahmati, Hamideh; Monirpoor, Nader; Besharat, Mohammad Ali; Hassanabadi, Hamidreza (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to model premature ejaculation disorder based on body image with the mediating role of attachment and narcissism. The study employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population included all married men in Tehran in 2024, from whom 250 participants were selected through convenience sampling. The research instruments included the Premature Ejaculation Diagnostic Tool (Symonds et al., 2007), the Body Image Questionnaire (Fisher, 1970), the Adult Attachment Scale (Collins & Read, 1996), and the Narcissistic Personality Inventory (Ames et al., 2006). Data were analyzed using SPSS-24 and AMOS-24 software. The findings indicated that the body image had a significant direct effect on premature ejaculation. In addition, body image had a significant indirect effect on premature ejaculation through avoidant attachment style (p < 0.001). However, narcissism did not show a significant effect. The results suggest that premature ejaculation disorder is not merely a biological phenomenon but is also influenced by psychological factors related to body perception, attachment patterns, and personality traits. Enhancing positive body image and modifying maladaptive attachment styles may be effective components in psychological interventions for this disorder.